Proteomics: a reality-check for putative stem cells - Prokopi, Marianna; Mayr, Manuel (My University, 2011)
The concept of using stem cells for cardiovascular repair holds great potential, but uncertainties in preclinical experiments must be addressed before their therapeutic application. Contemporary proteomic techniques can help to characterize cell preparations more thoroughly and identify some of the potential causes that may lead to a high failure rate in clinical trials. The first part of this review discusses the broader application of proteomics to stem cell research by providing an overview of the main proteomic technologies and how they might help the translation of stem cell therapy. The second part focuses on the controversy about endothelial progenitor cells (EPCs) and raises cautionary flags for marker assignment and assessment of cell purity. A proteomics-led approach in early outgrowth EPCs has already raised the awareness that markers used to define their endothelial potential may arise from an uptake of platelet proteins. A platelet microparticle-related transfer of endothelial characteristics to mononuclear cells can result in a misinterpretation of the assay. The necessity to perform counterstaining for platelet markers in this setting is not fully appreciated. Similarly, the presence of platelets and platelet microparticles is not taken into consideration when functional improvements are directly attributed to EPCs, whereas saline solutions or plain medium serve as controls. Thus, proteomics shed new light on the caveats of a common stem cell assay in cardiovascular research, which might explain some of the inconsistencies in the field.
Keywords: Angiogenesis; Differentiation; Platelets; Progenitor cells; Proteomics; Stem cells